Rabbit rearing in Algeria: family farms in the Tizi-Ouzou area - Berchiche M.; Lebas F. (Rabbit production in hot climates, 1994)
The aim of this work was to investigate the characteristics of traditional rabbit production in the Tizi-Ouzou area in Algeria. Data from a survey of 224 family farms and breeding performances from a breeding trial in a rural area were analysed. Small scale rabbit breeding is an inexpensive source of meat for the family but is limited by the summer heat and feed resources. Farmers were receptive to improved production methods (pure bred breeding stock and wire cages). However, technical support is essential if rabbit production is to take off.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)